A Study on the Effect of pH Value of Impregnation Solution in Nickel Catalyst Preparation for Methane Dry Reforming Reaction. Issue 31 (16th August 2019) - Li, Hangjie; Cheng, Shilin; He, Yingluo; Javed, Mudassar; Yang, Guohui; Yang, Ruiqin; Tsubaki, Noritatsu
Abstract: The nickel particle size, distribution and interaction with support are crucial to the catalytic performance in dry reforming of methane reaction (DRM). Despite numerous literatures on dry reforming catalysis, the effect of solution pH on the catalytic performance is not well studied. Herein, we designed a series of Ni/SiO2 catalysts with different Ni particle sizes. The Ni particle size was controlled with altering the pH of the Ni nitrate solution via the addition of HNO3 or NH4 OH. X‐ray diffraction (XRD) revealed that NH4 OH promoted Ni/SiO2 catalysts present smaller NiO nanoparticles, and enhanced metal‐support interaction was evidenced from X‐ray photoelectron spectra (XPS) and H2 temperature‐programmed reduction (H2 ‐TPR) analyses. In addition, according to thermogravimetric analysis and differential scanning calorimetry (TG‐DSC) and transmission electron microscopy (TEM) results, the spent catalysts produced less carbon deposition and maintained Ni nanoparticles in smaller size after DRM reaction. Catalysts with nearly uniform and small particle size demonstrated a satisfying resistance to aggregation and carbon deposition, while realizing a high CH4, CO2 and Ctotal conversion (74.5, 83.7 and 79.7%, respectively). The present study provides a simple but effective way to change the metal‐support interaction and metal particle size. Abstract : pH value of impregnation solution significantly controls the Ni particle size. Generally, the catalysts prepared under acid condition present bigger Ni particle size, while the catalysts prepared using NH4 OH solution exhibit smaller particle size and stronger metal‐support interaction, which demonstrate stable reaction activity due to excellent resistance to carbon deposition and metal sintering during dry reforming reaction.